До проблеми формування базової професійної компетентності майбутніх бакалаврів машинобудівних спеціальностей у процесі науково-природничої підготовки - Асєєва, Ірина Володимирівна (Класичний приватний університет, 2016)
У статті проаналізовано проблему якісної підготовки майбутніх бакалаврів машинобудівних спеціальностей у системі вищої професійної освіти. Наголошено на необхідності вдосконалення в них професійної компетентності у зв’язку з розвитком технологічного виробництва та потребами у фахівцях на ринку праці. Обґрунтовано значення процесу науково-природничої підготовки майбутніх бакалаврів машинобудівних спеціальностей у формуванні базової професійної компетентності.

the changing production conditions is explained in the article. It emphasizes the need to form basic professional competence of the future bachelors of mechanical-engineering specialties in connection with the development of technological production and also the need of specialists in the labor market. The competent specialist is able to perform various production problems, to analyze the situation, to make decisions, to evaluate their results, it is also important to be able to choose the necessary information and to be engage in the professional self-development. The value of the process of scientific and natural training in the formation of the basic professional competence, which is necessary for any technical education, as well as for the future bachelors of mechanical-engineering specialties, is proved in the article. The aim of scientific and natural training is the readiness of a future bachelor of techanical-engineering specialties to continuous self-education and to the practical application of the knowledge that was gained during the educational process as a result of training in a technical high school. The study of the disciplines of scientific and natural training contributes not only tothe acc umulation of the system of knowledge, competencies and skills, but also it contributes to the intellectual development of the future bachelors of mechanical-engineering specialties,and also at the same time it contributes to the formation of the basic professional competence.
On the Problem of the Formation of a Basic Professional Competence of the Future Bachelors of Mechanical-engineering Specialties in the Process of Scientific and Natural Training
Keywords: вища освіта; базова професійна компетентність; майбутні бакалаври; машинобудівні спеціальності; науково-природнича підготовка; higher education; basic professional competence; future bachelors; mechanical-engineering specialties; scientific and natural training